2020
DOI: 10.3390/s20236992
|View full text |Cite
|
Sign up to set email alerts
|

Gait Analysis with Wearables Can Accurately Classify Fallers from Non-Fallers: A Step toward Better Management of Neurological Disorders

Abstract: Falls are the leading cause of mortality, morbidity and poor quality of life in older adults with or without neurological conditions. Applying machine learning (ML) models to gait analysis outcomes offers the opportunity to identify individuals at risk of future falls. The aim of this study was to determine the effect of different data pre-processing methods on the performance of ML models to classify neurological patients who have fallen from those who have not for future fall risk assessment. Gait was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 69 publications
0
33
0
Order By: Relevance
“…A frailty prevalence study [ 48 ] observed differences in the pattern and variability of all elderly walking. Frail individuals had a more significant number of shorter walking sessions and less variable in walking bout duration than non-frail older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A frailty prevalence study [ 48 ] observed differences in the pattern and variability of all elderly walking. Frail individuals had a more significant number of shorter walking sessions and less variable in walking bout duration than non-frail older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Frail individuals had a more significant number of shorter walking sessions and less variable in walking bout duration than non-frail older adults. All these features may be restricted to activities entailing short walking bouts (i.e., within the home environment), and they may be unable to sustain prolonged bouts of walking [ 48 ]. Furthermore, as Ternero-Quiñones et al [ 49 ] point out, frailty and the risk of falls are significant predictors of autonomy in basic daily life activities.…”
Section: Discussionmentioning
confidence: 99%
“…For the topic of falls, we identified 24 studies that met inclusion criteria. Of these studies, eight used a retrospective cohort design 40 41 42 43 44 45 46 47 ; seven used a prospective cohort design 48 49 50 51 52 53 54 ; six were secondary analyses of research data obtained from prospective, retrospective, and cross-sectional studies 55 56 57 58 59 60 ; one used mixed methods wherein data from a public dataset were used in conjunction with measurements collected from sensors 61 ; and one was a meta-analysis of prospective cohort and observational studies. 62 Ten of the studies used health records as a source of data but in two of these studies, 44 47 it was not clear whether the records were electronic when they were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Several of the studies, including two of the secondary analyses, incorporated data from mobility and gait sensors. 48 49 51 53 55 60 61 Registries and administrative datasets were used in eight studies, 40 41 42 43 45 46 50 56 while questionnaires or surveys were a source of data for four studies. 49 51 57 60 With the exception of one study that employed sensor data from 17-year-old persons, 55 all study participants were community dwelling, inpatient, and outpatient adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation